Case Report: The importance of early intervention for gastroesophageal reflex disease caused by hiatal hernia - Kakiuchi, Toshihiko; Obata, Satoshi; Koji, Azusa; Minematsu, Nobuya; Fuchigami, Maho; Fukuta, Atsuhisa; Tajiri, Tatsuro; Yoshiura, Masato (Frontiers in Pediatrics, 2024)
Background: Gastroesophageal reflux (GER) disease (GERD) is a condition wherein GER causes troublesome symptoms that can affect daily functioning and/or clinical complications within the esophagus or other systems. To avoid this, patients with GERD often require treatment; hence, it is important to distinguish GER from GERD. Patients with GERD exhibiting alarm signs should be examined early to differentiate it from GER and treated accordingly. Herein, we present a case of GERD caused by a hiatal hernia that required surgical intervention for esophagial cicatrical stenosis despite oral treatment. We also discussed how to choose the appropriate acid suppressants for GERD.Case Presentation: A 1-year-old boy was referred to our hospital for repeated vomiting and poor weight gain. He received histamine 2 receptor antagonists (H2RAs) that contributed slightly to the decreased frequency of vomiting and aided weight gain; however, he soon stopped gaining weight and had bloody vomit. His upper gastrointestinal series revealed hiatal hernia, a 24-hour impedance pH monitoring test indicated abnormal values for acid reflux, and esophagogastroduodenoscopy (EGD) revealed esophagitis. He was subsequently diagnosed with GERD associated with hiatal hernia. A proton pump inhibitor (PPI) was intravenously administered to him, following which his medication was changed to a potassium-competitive acid blocker (P-CAB). Thereafter, his vomiting episodes significantly decreased and his weight increased. However, 6 months after starting P-CAB, his vomiting episodes suddenly increased in frequency. EGD revealed the presence esophageal stricture due to scarring from GERD. He was then treated via laparoscopic fundoplication, gastrostomy, and esophageal balloon dilation. Thereafter, his vomiting episodes stopped and food intake improved, leading to weight gain.It is essential to identify the cause of GERD early and take an appropriate treatment approach depending on the cause of GERD with alarm signs. further, as a drug therapy for GERD as a clear acid mediated disease or in children with alarm signs, PPIs or P-CAB should be used from the beginning instead of H2RAs.